Surviving digital transformation era through strategic entrepreneurship with collaborative innovation between bank and fintech - Shanti Rachmawati Rachmawati Putri; Avanti Fontana (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
With the emergence of financial technology (Fintech) players, nowadays, Banks need to be more flexible and faster to respond effectively to customers' growing needs in dynamic and even disruptive markets. The tendency of established banking solely leans on their existing competitive advantage impacting their deficient capability when exploring new business opportunities. Therefore, banks need strategic tools to enhance their exploration capability and increase business innovation performance. In this instance, the innovation process must be fluid, embracing open-collaborative innovation, which extends beyond internal activities, such as start-up collaboration. Collaborative innovation with start-ups like Fintech is critical to excel in digital transformation to provide services that suit consumers' demands and stakeholders. This study addresses the effects of strategic entrepreneurship and collaborative innovation performance in Indonesia's banking industry. This study has used questionnaires developed from a previous study, which enables respondents to display favorable or unfavorable attitudes toward the object of interest. This study was conducted through a survey method. Data were collected using questionnaires distributed to seventy-two managers and top-level management of the banking-based industry in Indonesia. Surveys are analyzed by using Structural Equation Modelling (SEM) analysis with Partial Least Square (PLS) method to assess the structural model (hypotheses). For further study, the researcher should consider the limitation presented in this paper in terms of context and case of the study, as well as a new perspective of research design.